2019
DOI: 10.1038/s41598-019-56442-7
|View full text |Cite
|
Sign up to set email alerts
|

Murine fecal microbiota transplantation lowers gastrointestinal pathogen loads and dampens pro-inflammatory immune responses in Campylobacter jejuni infected secondary abiotic mice

Abstract: Conventional mice are protected from Campylobacter jejuni infection by the murine host-specific gut microbiota composition. We here addressed whether peroral fecal microbiota transplantation (FMT) might be an antibiotics-independent option to lower even high gastrointestinal C. jejuni loads in the infected vertebrate host. To address this, secondary abiotic mice were generated by broad-spectrum antibiotic treatment and perorally infected with C. jejuni by gavage. One week later, mice were stably colonized with… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 43 publications
3
8
0
Order By: Relevance
“…We also found that the number of T cells (CD8 + , CD4 + , γδ and NKT) were increased at d10 post-infection in the liver (data not shown). Our results agree with previous studies showing increases in T cells in the liver d10 post-Tg infection [87], as well as a general increase in liver pathology, infiltrates and inflammation [88].…”
Section: Discussionsupporting
confidence: 93%
“…We also found that the number of T cells (CD8 + , CD4 + , γδ and NKT) were increased at d10 post-infection in the liver (data not shown). Our results agree with previous studies showing increases in T cells in the liver d10 post-Tg infection [87], as well as a general increase in liver pathology, infiltrates and inflammation [88].…”
Section: Discussionsupporting
confidence: 93%
“…Adult wildtype mice harboring a conventional gut microbiota, for instance, are protected from stable C. jejuni colonization even following peroral infection with high bacterial loads [17]. This physiological colonization resistance provided by the intact complex murine gut microbiota is abrogated upon broad-spectrum antibiotic treatment, however, rendering mice susceptible to intestinal C. jejuni colonization following peroral pathogenic challenge [18][19][20]. This also holds true for conditions that are accompanied by gut microbiota shifts towards elevated intestinal loads of commensal enterobacteria, including Escherichia coli [16,21].…”
Section: Introductionmentioning
confidence: 99%
“…In summary, our present study revealed that peroral C. coli infection results in pronounced clinical signs, apoptotic, and pro-inflammatory immune responses in the intestinal tract of IL-10 −/− mice harboring a human intestinal microbiota, whereas IL-10 −/− mice with a murine intestinal microbiota were stably colonized by the pathogen, but protected from disease manifestations. Given that murine FMT treatment could effectively dampen pathogen-induced apoptotic epithelial and pro-inflammatory immune responses in the large intestines of C. jejuni -infected microbiota-depleted, as well as of “humanized”, IL-10 −/− mice [ 27 , 31 ], these findings collectively provide strong evidence that microbiota modifications by pre- or probiotics, for instance, might open novel avenues for future treatment strategies in the combat of campylobacteriosis in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Our cultural analyses and culture-independent molecular approaches additionally assessing fastidious and non-cultivable bacteria revealed, however, that the host-specific differences in numbers of the most common intestinal bacterial groups, genera, and species between respective fecal donor suspensions could also be observed in the intestinal tract of IL-10 −/− mice after establishment of the complex human versus murine intestinal microbiota following peroral FMT. Even though the methods applied here have their limitations regarding the possibilities to provide a complete picture of the commensal ecological conditions within the gut lumen, the combinatory approach of quantitative “culturomics” plus 16S rRNA-based analyses have been proven highly reliable for a comprehensive survey of differences in host-specific intestinal microbiota compositions [ 15 , 16 , 24 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. One needs to take into account, however, that during processing of the fecal donor samples, including freezing and thawing, individual bacterial strains might have been reduced and not fully established within the intestinal tract upon FMT [ 27 , 30 , 35 ].…”
Section: Discussionmentioning
confidence: 99%